2014
DOI: 10.1371/journal.pone.0100591
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Glutamic Acid in Piglets Challenged with Deoxynivalenol

Abstract: The mycotoxin deoxynivalenol (DON), one of the most common food contaminants, primarily targets the gastrointestinal tract to affect animal and human health. This study was conducted to examine the protective function of glutamic acid on intestinal injury and oxidative stress caused by DON in piglets. Twenty-eight piglets were assigned randomly into 4 dietary treatments (7 pigs/treatment): 1) uncontaminated control diet (NC), 2) NC+DON at 4 mg/kg (DON), 3) NC+2% glutamic acid (GLU), and 4) NC+2% glutamic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 56 publications
3
51
0
Order By: Relevance
“…These results are in agreement with previous studies that suggested that oxidative stress may be owing to the direct effect of these mycotoxins, their metabolites and/or the generated free radicals (Abdel-Wahhab et al, 2010;Kanbur et al, 2011;Wu et al, 2014). Strikingly, the combined AFB1 + DON presented a synergetic effect on MDA, while AFB1 + ZEA presented antagonistic effects on both T-AOC and MDA, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with previous studies that suggested that oxidative stress may be owing to the direct effect of these mycotoxins, their metabolites and/or the generated free radicals (Abdel-Wahhab et al, 2010;Kanbur et al, 2011;Wu et al, 2014). Strikingly, the combined AFB1 + DON presented a synergetic effect on MDA, while AFB1 + ZEA presented antagonistic effects on both T-AOC and MDA, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, the hepatotoxicity of DON was manifested by the significant increase of serum ALT, AST and ALP activity which consider good indicators of hepatic injury (Kasmani et al, 2012) and suggested that DON disturbed the cell membrane resulting in the leakage of these enzymes in serum . These results are similar to the previous studies which provided evidence that DON induced liver injury (Jiang et al, 2011;Wu et al, 2013) and suggested that oxidative stress induced by the mycotoxin or its metabolites has a direct effect on hepatic cell membrane Kanbur et al, 2011;Wu et al, 2014;Sun et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Osselaere et al verified that this mycotoxin causes oxidative stress in the small intestine of chicken after exposure to DON at 7.54 mg kg −1 . Wu et al demonstrated, in swine, that the ingestion of chow contaminated with 4 mg kg −1 of DON causes evident oxidative stress. In this way, the effects of DON on the formation of free radicals and on anti‐oxidant defenses depend on dose and length of exposure.…”
Section: Discussionmentioning
confidence: 99%